Park characteristics influences to physical activity among overweight adolescents - Danis, Ajau; Sidek, Suriati; Md. Yusof b, Safiah (AMER (Association of Malaysian Environment-Behaviour Reseachers), ABRA (Association of Behavioural Researchers on Asians), and Universiti Teknologi MARA, Malaysia, 2016)
The link between environmental characteristics of neighbourhood parks and adolescents’ physical activity is poorly understood. Therefore, the present study aims to explore the environmental characteristics of the neighbourhood parks that influence physical activity from the perception of overweight adolescents. In-depth semi-structured interviews with 20 overweight adolescents between 13 and 17 years old successfully done. Interviews recorded, transcribed and analyzed based on a thematic content analysis. The results showed that physical and social environment influenced physical activity and neighbourhood parks usage. It is essential to consider these environmental characteristics in developing physical activity intervention that aims to promote physical activity among overweight adolescents.